COPPER RECOVERY FROM LOW GRADE ORES, CONCENTRATES AND TECHNOGENIC WASTE BY AMMONIA LEACHING - AN OLD IDEA WITH PROMISING FUTURE: COPPER RECOVERY FROM LOW GRADE ORES, CONCENTRATES AND TECHNOGENIC WASTE BY AMMONIA LEACHING - AN OLD IDEA WITH PROMISING FUTURE - Panayotova, Marinela; Panayotov, Vladko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Sustainable development of the society and our everyday life increasingly needs copper. To meet this demand impoverished ores, low-grade concentrates and technogenic waste have to be processed. For these raw materials the classical route ’’mineral processing - pyrometallurgy’’ is inapplicable and / or unprofitable. Leaching followed by recovery from the obtained solutions is increasing being applied worldwide. Ammonia leaching is progressively finding its use, especially when ores are carbonaceous and / or oxidized. The paper presents development of ammonia leaching and its nowadays application for copper recovery, including leaching technological conditions, leaching kinetics and means for copper recovery from pregnant leach solutions with an emphasis on solvent extraction and the latest development in the area.